Late-onset nephrotic syndrome with thyroid hypoplasia and nup85 mutation in Galloway-Mowat syndrome: A case report (Indian Journal of Case Reports, 2021)
Galloway-Mowat syndrome is an autosomal recessive rare hereditary disorder with progressively worsening renal function, neurological and psychomotor abnormalities, microcephaly, facial dysmorphism, and thyroid, adrenal, and ovarian hypoplasia/agenesis. Here, we present the case of a 9-year-old girl who presented with late-onset steroid-resistant nephrotic syndrome with rapid worsening of renal function, microcephaly, hypertelorism, high-arched palate, delayed speech and developmental milestones, poor intellectual function, short stature, hypertension, and hypothyroidism. Magnetic resonance imaging brain was suggestive of cerebral and cerebellar atrophy, hypomyelination, and optic atrophy. Renal biopsy was suggestive of focal segmental glomerulosclerosis. Whole-genome exon sequencing revealed a homozygous mutation in the NUP85 gene. The clinicians should be aware of this rare syndrome and consider it as a possibility in any patient presenting with nephrotic syndrome, microcephaly, and neurological abnormality.